A semiconductor radiation imaging pixel detector for space radiation dosimetry. (July 2015) - Kroupa, Martin; Bahadori, Amir; Campbell-Ricketts, Thomas; Empl, Anton; Hoang, Son Minh; Idarraga-Munoz, John; Rios, Ryan; Semones, Edward; Stoffle, Nicholas; Tlustos, Lukas; Turecek, Daniel; Pinsky, Lawrence
Abstract: Progress in the development of high-performance semiconductor radiation imaging pixel detectors based on technologies developed for use in high-energy physics applications has enabled the development of a completely new generation of compact low-power active dosimeters and area monitors for use in space radiation environments. Such detectors can provide real-time information concerning radiation exposure, along with detailed analysis of the individual particles incident on the active medium. Recent results from the deployment of detectors based on the Timepix from the CERN-based Medipix2 Collaboration on the International Space Station (ISS) are reviewed, along with a glimpse of developments to come. Preliminary results from Orion MPCV Exploration Flight Test 1 are also presented.